PENERAPAN METODE MOORA-WASPAS PADA SISTEM PENENTUAN CALON PENERIMA SUBSIDI TUNJANGAN FUNGSIONAL GURU BPNS DI SMA TAMANSISWA TAPIAN DOLOK - Afira Zulfa; Ilka Zufria; Triase Triase (UIN Sumatera Utara Medan, 2021)
The determination of the recipients of functional allowance subsidies for non-civil servant teachers at SMA Tamansiswa Tapian is done manually with no weighting of criteria which means that the teachers who will be selected are not based on the best abilities and criteria so that the system that runs is not appropriate and efficient. In order for the teacher's functional allowance to be properly targeted, it is necessary to implement a decision support system to handle it automatically. Teachers who receive the functional allowance subsidy are eligible once a year so that the election is conducted annually and the system can be used continuously. The combination of the MOORA and WASPAS methods in the decision support system is able to determine the best value from the assessment of 5 criteria with a predetermined weight. This system can rank the highest to the lowest scores of each teacher as a candidate for the functional allowance subsidy.